Antihydrogen in a bottle - Stefan Eriksson (Physics Education, 2013)
We describe recent experiments at CERN in which antihydrogen, an atom made entirely of antimatter, has been held in a magnetic minimum neutral atom trap and subjected to microwave radiation to induce a resonant quantum transition in the anti-atom. We discuss how this, the first experiment to observe an interaction between an antihydrogen atom and a photon, was achieved. We provide some background to antimatter physics and cover aspects of the current motivation for our experiments.